Ammonia‐Borane Derived BN Fragments Trapped on Bi‐ and Trimetallic Titanium(III) Systems. Issue 29 (30th April 2019) - del Horno, Estefanía; Jover, Jesús; Mena, Miguel; Pérez‐Redondo, Adrián; Yélamos, Carlos
Abstract: Titanium(III) complexes containing unprecedented (NH2 BH2 NHBH3 ) 2− and {N(BH3 )3 } 3− ligands have been isolated, and their structures elucidated by a combination of experimental and theoretical methods. The treatment of the trimethyl derivative [TiCp*Me3 ] (Cp*=η 5 ‐C5 Me5 ) with NH3 BH3 (3 equiv) at room temperature gives the paramagnetic dinuclear complex [{TiCp*(NH2 BH3 )}2 (μ‐NH2 BH2 NHBH3 )], which at 80 °C leads to the trinuclear hydride derivative [{TiCp*(μ‐H)}3 {μ3 ‐N(BH3 )3 }]. The bonding modes of the anionic BN fragments in those complexes, as well as the dimethylaminoborane group trapped on the analogous trinuclear [{TiCp*(μ‐H)}3 (μ3 ‐H)(μ3 ‐NMe2 BH2 )], have been studied by X‐ray crystallography and density functional theory (DFT) calculations. Abstract : BN bridge : Titanium(III) complexes containing unprecedented (NH2 BH2 NHBH3 ) 2− and {N(BH3 )3 } 3− bridging ligands have been isolated by treatment of the trimethyl derivative [Ti(η 5 ‐C5 Me5 )Me3 ] with NH3 BH3 .